Treatment Exit Options for Non-infectious Uveitis (TOFU): Study Protocol for a Prospective Clinical Registry. (2nd January 2022) - Li, Jeany Q.; Heinz, Carsten; Dell, Jennifer; Schmid, Matthias; Finger, Robert P.
ABSTRACT: Purpose: Currently, there is limited evidence regarding clinical management of non-anterior non-infectious uveitis including treatment outcomes of disease-modifying anti-rheumatic drugs (DMARDs) and their combinations. Treatment guidelines or recommendations on preferred choice of DMARD combinations and reduction and/or discontinuation strategies in quiescent uveitis are lacking. The TOFU (Treatment exit options for non-infectious uveitis) registry aims to document disease courses and to provide recommendations on DMARD treatment exit strategies. Methods: The registry is an observational, non-commercial, and non-interventional study and targets patients who are ≥18 years of age with non-infectious uveitis of the posterior segment or retinal vasculitis on or starting DMARD treatment. Data are entered prospectively at study sites through a web-based interface into electronic case report forms (eCRF) implemented in the electronic data capture software RedCap (Version 9, Vanderbilt University, USA). The collated data include ophthalmological, general medical history and patient-reported outcomes (PROs). Assessment of uveitis classification and activity follows the international Standardization of uveitis nomenclature (SUN) criteria. Patient appointment and treatment decisions remain at the discretion of the managing physician and are completely independent of participation in the registry. The study follows the tenets of the declaration of Helsinki. Conclusions: The TOFU registry captures real-life data of patients with non-infectious uveitis of the posterior segment, involving both medical personnel and patients. The study adheres to international standards and will provide important evidence and guidance in the development of guidelines.